Comparative ethnopharmacological survey: Medicinal plants and remedies for oral health in Meknes, Morocco, and their limits facing modern dentistry - Asmae Benabderrahmane; Majid Atmani; Wijdane Rhioui; Abdellatif Boutagayout; Saadia Belmalha (GarVal Editorial Ltda., 2024)
Context: For centuries, herbal remedies have been widely used to alleviate and prevent oral pathologies. Aims: To compare the herbalists' knowledge with that of the local population, their prevalence of the use of modern non-pharmacological medicine, and investigate the traditional knowledge of the use of medicinal and aromatic plants for oral health in Meknes, Morocco. Methods: A cross-sectional survey was conducted using a structured questionnaire. Along with medicinal plants, other remedies such as alum, salt, and vinegar have also been investigated. Statistical calculations by use value, relative frequency of citation, family use value, informant consensus factor, and fidelity level were performed and compared between the two groups. Results: Numerous medicinal plant species were identified for oral health, namely Syzygium aromaticum, Juglans regia, and Ammi visnaga. Most participants reported using these plants to treat and prevent dental caries, gingivitis, and toothache. Herbalists were found to have a greater knowledge of plants and their uses than the general population. However, a significant proportion of participants, including herbalists, opted for modern medicine or dental care and extraction as treatments of choice, combined or not with traditional treatments. Conclusions: This study emphasizes the rich understanding of medicinal plants for oral health, underscoring herbalists' role as key informants on traditional plant usage for various oral diseases. The populace's increasing reliance on modern dental treatments highlights the limitations of natural remedies for severe oral conditions. Nonetheless, integrating these plants alongside modern dentistry can optimize oral health prevention strategies.